Effect of post oxidation annealing in nitric oxide on interface properties of 4H-SiC/SiO2 after high temperature oxidation - 李妍月 邓小川 刘云峰 赵艳黎 李诚瞻 陈茜茜 张波 (半导体学报：英文版, 2015)
The interface properties of 4H-SiC metal oxide semiconductor （MOS） capacitors with post-oxidation annealing （POA） in nitric oxide （NO） ambient after high temperature （1300 ℃） oxidation have been investigated using capacitance-voltage （C V） measurements. The experimental results show that the interface states density （Dit） can be obviously decreased by the POA in NO ambient （NO-POA） and further reduced with increasing POA temperature and time. In the meantime significant reduction of the interface states density and oxidation time can be achieved at the higher thermal oxidation temperature, which results in the better oxide MOS characteristics and lower production costs. The dependence of Dit on POA temperature and time has been also discussed in detail.